Human security and governance: Indonesian illegal migrant workers in Malaysia - Rahimi Ahmad; Aizat Khairi (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the migration of Indonesian workers to Malaysia, with a specific focus on irregular migrants. Despite Indonesia’s economic growth, factors such as unemployment, low wages, and limited opportunities in rural areas continue to drive migration. Utilising an integrated framework that combines economic incentives and human security dimensions, this research analyses seven components of human security: economic, food, health, social, personal, community, and political security. Primary data, including face-to-face interviews with key stakeholders, underscores this phenomenon's personal and systemic dimensions. Findings reveal that socio-economic challenges in Indonesia act as push factors, while wage disparities and economic prospects in Malaysia serve as pull factors. However, these benefits come with challenges, such as xenophobia, integration difficulties, and societal instability in the host country. This study highlights the limited efficacy of enforcement measures like deportations and suggests policy reforms addressing root causes. This research contributes to understanding irregular migration governance within a human security framework, offering insights into Malaysia’s policy responses.